2018
DOI: 10.1016/j.flatc.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial two-layer graphene under pressure: Diamene stiffer than Diamond

Abstract: The unprecedented ultrahigh interlayer stiffness of supported two-layer epitaxial graphene on silicon carbide (SiC) has been recently reported by our research group. We found that under localized pressure a two-layer epitaxial graphene behaves as an ultra-hard and ultrastiff coating, showing exceptional mechanical properties that far exceed those of bare SiC. Density functional theory (DFT) calculations indicate that this unique behavior stems from a sp 2-to-sp 3 reversible phase transition of carbon films und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 21 publications
4
50
0
Order By: Relevance
“…High-pressure experiments with bi-and multilayered graphanes show the formation of 2D diamond structures [56,57]. These kinds of diamanes without adsorbents on the surfaces, named diamondenes [56], could serve as diamond seeds in nanoheterostructures and rocks subjected to high pressures.…”
Section: Moiré Diamanes-theoretical Studiesmentioning
confidence: 99%
“…High-pressure experiments with bi-and multilayered graphanes show the formation of 2D diamond structures [56,57]. These kinds of diamanes without adsorbents on the surfaces, named diamondenes [56], could serve as diamond seeds in nanoheterostructures and rocks subjected to high pressures.…”
Section: Moiré Diamanes-theoretical Studiesmentioning
confidence: 99%
“…The indentation modulus measured for the 2D films is compared with the stiffness of the substrate as well as the stiffness of other ultra-stiff reference materials, namely CVD (001) diamond film obtained through a HFCVD process [65], SiC (0001), and bulk (0001) sapphire [11]. The spectral clustering algorithm discussed in the Methods section is used to isolate graphene domains in phase imaging data coupled with topographic scans in both exfoliated graphene flakes and epitaxial graphene films.…”
Section: å-Indentation For Transverse Elasticity Of 2d Layersmentioning
confidence: 99%
“…The extremely small indentation depth utilized during MoNI/ÅI has enabled for the first time the study of the transverse elasticity of few layer thick graphene films 19 . In particular, indentation depths in the order of few tenths of an Ångstrom have been employed to probe the interlayer stiffness of epitaxial graphene and epitaxial graphene oxide, and, more recently, to demonstrate the ultra-high stiffness of 2-layer epitaxial graphene 35 , 36 . These experiments showed that Van der Waals interactions between different layers play an important role in determining the stiffness of the material when a force is applied perpendicular to the principal planes of graphene.…”
Section: Moni/åi Applied To Ultra-thin and Ultra-hard Filmsmentioning
confidence: 99%
“…MoNI/ÅI has recently found applications in the characterization of the mechanical properties of the transverse mechanical stiffness of supported 2D materials, and in particular supported epitaxial graphene 19 , 35 . The enhanced resolution of MoNI/ÅI has enabled for the first time the direct measurement of the inter-layer stiffness of few layer thick graphene and graphene oxide supported films 19 and has led to the discovery of the room-temperature diamondization of epitaxial bi-layer graphene on silicon carbide 35 , 36 . These measurements have been possible only due to the extremely high spatial resolution of MoNI/ÅI.…”
Section: Introductionmentioning
confidence: 99%